Methods and Algorithms for Knowledge Reuse in Multiagent Reinforcement Learning - da Silva, Felipe Leno; Costa, Anna Helena Reali (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2020)
Reinforcement Learning (RL) is a powerful tool that has been used to solve increasingly complex tasks. RL operates through repeated interactions of the learning agent with the environment, via trial and error. However, this learning process is extremely slow, requiring many interactions. In this thesis, we leverage previous knowledge so as to accelerate learning in multiagent RL problems. We propose knowledge reuse both from previous tasks and from other agents. Several flexible methods are introduced so that each of these two types of knowledge reuse is possible. This thesis adds important steps towards more flexible and broadly applicable multiagent transfer learning methods.